Implementasi Openbravo pada Proses Transaksi Penjualan, Produksi dan Sistem Inventory (Studi Kasus PT. NUSANTARA BETA FARMA) - Fajril Akbar; Ricky Akbar; Mardaleni .; Netti . (Jurnal Nasional Teknologi dan Sistem Informasi, 2015)
PT. Beta Farma Nusantara (NBF) is a company that produces and sales of drugs and cosmetics. NBF has 1 factory and many administrative offices that located in many big cities in Indoenesia. NBF consists of the production division, sales division, inventory division, human resource management, finance and quality control division. Nowadays, every business processes within each division are separately processed and it caused ineffective and inefficiency. Enterprise Resource Planning (ERP) is an information system solution that can integrate all bussines process of the company using computerization. The proposed system used Openbravo as system integrator, automation and it had multi-site capability. In this research, we focussed to implement the system only in sales, production and inventory division at NBF.  The experiment is validated by comparing existing reports with reports generated with Openbravo. We also measured the running time using exising system and the proposed system. The result show the generated report has the same format and it takes less processing time with an average running time of the business processes in the system of sales, production and inventory NBF are   ± 5 minutes.